METHODS FOR IMPROVING THE EFFICIENCY OF SMART EDUCATIONAL TECHNOLOGIES IN THE EDUCATION SYSTEM - Abdukadirova, Gulbahor (Educational Research in Universal Sciences, 2023)
In this article, we have explained that in the digital age we live in, “smart learning” is a broad term for education that offers ample opportunity to improve the effectiveness of education. This allows people to learn new skills and information more easily, faster and more efficiently. The global movement towards smart learning is bringing about major changes in how people learn today, as well as in the processes that help smart learning do great things in the learning process.